Analisis Kemampuan Penalaran Matematis Siswa Kelas VII Berdasarkan Gaya Kognitif Field Independent dan Dependent - Huda, Syaiful; Mujib, Abdul; Ramdhani, Sendi (Jurnal Didaktika Pendidikan Dasar, 2024)
The research was motivated by the importance of reasoning skills possessed by seventh grade students when solving a problem using differences in the way students capture and process information. Therefore, the purpose of this study was to analyze students’ mathematical reasoning ability in solving algebraic story problems in terms of Field Independent (FI) and Field Dependent (FD) cognitive styles. Mixed methods with the sequential explanatory design were used in this study. The research sample was 127 students from 4 schools. The data collection instruments used Group Embedded Figure Test, description test and interview. The data were analyzed quantitatively and qualitatively. The indicators of mathematical reasoning measured include conjecture , the ability to perform mathematical manipulation , the ability to find mathematical patterns to make generalizations , the ability to check the validity/validation of conjectures , and the ability to draw conclusions from statements . Based on the results of the analysis, there is no difference in mathematical reasoning ability between students with FI and FD cognitive styles in solving algebraic story problems. While the mathematical reasoning ability of students in terms of cognitive style, students with cognitive style FI and FD have a tendency of mathematical reasoning to the level of deductive logic.